Low-dose and high-dose naltrexone in opioid dependence syndrome: a three months outcome study - Ajeet Sidana; Subhash Das; Sai Prashant Bansal (Open Journal of Psychiatry and Allied Sciences, 2019)
Background: Naltrexone is effective in the treatment of opioid dependence syndrome (ODS) as it prevents relapse. To effectively design a cost-effective treatment modality for ODS using naltrexone as low as 25 mg is something which is worth exploring. Aim: To study the effectiveness of 25 mg naltrexone and 50 mg naltrexone in patients with ODS. Materials and methods: Case record files of patients of ODS admitted in psychiatry ward from January 2015 to September 2017 were retrieved and analysed after applying coding plan. Results: A total of 79 patients with ODS were admitted during this period. Patients were divided into three groups- group one received 25 mg naltrexone per day, group two: 50 mg naltrexone, and group three: non-naltrexone. Cumulative abstinence duration (CAD) in group one was 48 days, group two was 52 days, and group three was 23 days. At follow-up, there was no relationship between abstinence status and dose of naltrexone prescribed and amount of opioid use. Conclusion: Naltrexone is effective in reduction of craving and there was no significant difference between the different dosages of naltrexone, i.e. 25 mg and 50 mg per day.